Corrigenda and Addenda to Diels' Galenica by Richard J. Durling: III. Manuscripts and Editions - Fortuna, Stefania (Traditio, 2006)
Richard Jasper Durling (1932–1999) made many important contributions to the study of the Latin tradition and critical edition of the works of Galen (AD 129–216), the Greek physician who was a notable figure in the history of medicine from late antiquity to the eighteenth century.